FEATURES OF THE INTERFERON INDUCTOR – CELAGRIP - Arslonova Raikhon Rajabboevna; Ergasheva Dilnura Ulugbek daughter; Chuliboeva Rukhshona Toshniezovna (Journal Park Publishing, 2025)
Inflammation is the main pathogenetic component of many diseases of various etiologies and one of the most important problems of general pathology and clinical practice. It is a universal response of the body to the effects of various exogenous and endogenous damaging factors, which include pathogens of bacterial, viral and parasitic infections, as well as allergens, physical and chemical stimuli. They cause both local and general reactions.Inflammation, in turn, is a complex process regulated by many endogenous substances. The latter are produced by various cellular elements involved in inflammation (mast cells, polymorphonuclear leukocytes, monocytes, macrophages, endothelial cells, thrombocytes). They secrete such biologically active substances as prosthanoids, leukotrienes, NO, platelet-activating factor (PAF), histamine, some interleukins, etc. Therefore, the possibilities of pharmacological regulation of inflammation are quite diverse. Usually they come down to suppressing the production and release of substances that stimulate the inflammation process.(Kharkevich D.A., 2008).